China's Arctic policy: present and future. Issue 1 (2nd January 2019) - Mariia, Kobzeva
ABSTRACT: The article examines China's Arctic policy features and the meaning of the first published White Paper of 2018 for the future behaviours of the PRC. The author reviews the interests of the PRC in the High North, and the political objectives and means. The article pays special attention to the origins of Chinese policy in the Arctic, including the national strategy, expert discourse and regional specifics. The author discusses the role of the Chinese public and private actors for the implementation of national achievements in the circumpolar region. The article examines Chinese interpretations of key international documents regulating activities in the Arctic, and the significance of these interpretations for the implementation of the PRC policy. The special emphasis is made of the diplomacy features and the role of the 'soft' and 'hard' power when China is interacting with different actors. The author explores the interconnection of the White Paper 'China's Arctic policy' with the implementation of the 'Arctic Silk Road'. As an outcome, the author indicates principles explaining China's Arctic behaviours in the long-term perspective. Abbreviation: PRC: the People's Republic of China; UN: the United Nations; BRI: the Belt and Road Initiative; ASR: the Arctic Silk Road; LNG: liquefied natural gas; USA: the United States of America; SOA: the State Oceanic Administration; CNPC: the China National Petroleum Corporation; CNOOC: the China National Offshore Oil Corporation; COSCO: the China Ocean Shipping Company; UNCLOS: the United Nations Convention for the Law of the Sea; EU: the European Union; IMO: the International Maritime Organization; CNARK: the China-Nordic Arctic Research Center